Literature Review: Teacher Innovativeness in Learning in the Digital Era - Gresinta, Efri; Tukiran, Martinus (IJOSMAS, 2024)
Teachers play an important role in education because the teacher's character determines educational progress. To implement this, teacher innovation is needed which has a positive impact on the quality of education in learning in the digital era. This research is a qualitative descriptive study using the Systematic Literature Review (SLR) method, the aim is to analyze teacher innovation in learning in the digital era. In this research, the author uses literature sources that are relevant to the research such as articles, journals and documents. The results of the review of several articles show that teachers carry out various innovations in learning, namely by implementing a Smart Learning Project using digital-based applications and platforms, implementing games-based learning education or DGBL (Digital Games Based Learning) which can increase learning motivation. students, teachers can manage the class well, and the material and assignments are more challenging and varied. Teachers who have good self-confidence in using digital technology report that students' cognitive abilities become more active and the material presented becomes more interesting.